Factors Influencing Consumer Behaviour in Indofood Products during Covid-19 Pandemic - Jian, Oh Zi; Binti Ahmad, Siti Nur Madhiah; Sin, Liem Gai; Hoo, Chan Weng; Kee, Daisy Mui Hung; Hao, Jeremy Tou Jia; Chun, Leong Kar; Wee, Lim Xin; Valentine, Decesta Kelcya; Bin Azhar, Mohamad Fikri; Binti Abdullah, Norazwa; A/L Rajendran, Jeevendra (AIBPM Publisher, 2021)
The research aims to determine factors influencing consumer behaviour at PT Indofood Sukses Makmur Tbk during the Covid-19 pandemic. The data processed by analysing the psychological factors, social factors, cultural factors, personal factors and economic factors. A questionnaire survey was employed to collect the data. The questionnaire was distributed to 129 respondents via online platform. Secondary data research methods such as previous journals and reports from used to obtain relevant information in this research. The result showed that psychological factors are considered as factors that influence consumer behaviour in Indofood’s products during COVID-19 pandemic.